Reputation Shocks and Recovery in Public-Serving Organizations: The Moderating Effect of Mission Valence. (13th October 2020) - Willems, Jurgen; Faulk, Lewis; Boenigk, Silke
Abstract: This study investigates the impacts of negative and positive signals on public-serving organizations' reputations. We draw on sociocognitive perspectives to test how organizations' breaches of stakeholders' trust are repairable over time as well as the moderating effect of organizational mission valence on this forgiveness process. Multilevel data from two slope-shift experiments ( n = 304; n = 582) show that mission valence, or individuals' affinity with an organization's mission, intensifies the effects of both negative and positive signals in organizations' reputation building processes. Negative signals have stronger negative effects on intentions to support the organization for individuals with high mission valence. However, the effect of successive positive signals is also stronger for individuals with high mission valence, suggesting greater forgiveness following a stronger breach of trust among these stakeholders.